Membrane Protein Structures in Lipid Bilayers; Small-Angle Neutron Scattering With Contrast-Matched Bicontinuous Cubic Phases - Conn, Charlotte E.; de Campo, Liliana; Whitten, Andrew E.; Garvey, Christopher J.; Krause-Heuer, Anwen M.; van 't Hag, Leonie (Frontiers in Chemistry, 2021)
This perspective describes advances in determining membrane protein structures in lipid bilayers using small-angle neutron scattering. Differentially labelled detergents with a homogeneous scattering length density facilitate contrast matching of detergent micelles and this has been successfully used to obtain the structures of membrane proteins. However, detergent micelles do not mimic the lipid bilayer environment of the cell membrane in vivo. Using deuterated vesicles, the radius of gyration of membrane proteins can also be obtained, but protein-protein interference effects within the vesicles severely limits this method such that protein structure cannot be modelled. We show herein that different membrane protein conformations could be distinguished within the lipid bilayer of the bicontinuous cubic phase using contrast-matching. The time-resolved studies that have been performed using SANS illustrate the complex phase behaviour in lyotropic liquid crystalline systems and emphasize the importance of this development. We believe that studying membrane protein structures and phase behaviour in contrast-matched lipid bilayers will advance both biological and pharmaceutical applications of membrane-associated proteins, biosensors and food science.